2022
DOI: 10.1029/2022pa004451
|View full text |Cite
|
Sign up to set email alerts
|

Millennial‐Scale Climate Oscillations Triggered by Deglacial Meltwater Discharge in Last Glacial Maximum Simulations

Abstract: Our limited understanding of millennial‐scale variability in the context of the last glacial period can be explained by the lack of a reliable modeling framework to study abrupt climate changes under realistic glacial backgrounds. In this article, we describe a new set of long‐run Last Glacial Maximum experiments where such climate shifts were triggered by different snapshots of ice‐sheet meltwater derived from the early stages of the last deglaciation. Depending on the location and the magnitude of the forcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Therefore, there has been considerable interest in understanding the variability of the AMOC across timescales, from interannual to multidecadal (Buckley and Marshall, 2016) and millennial scales (Lynch-Stieglitz, 2017). For example, recently, several studies using comprehensive climate models found unforced millennial-scale AMOC oscillations under glacial boundary conditions (Vettoretti et al, 2022;Klockmann et al, 2020;Kuniyoshi et al, 2022;Romé et al, 2022), which resemble the Dansgaard-Oeschger events found in paleoclimate records. However, at intermediate, (multi-)centennial timescales, the variability of the AMOC has been studied less extensively, and we will focus on these timescales in the remainder of this study.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, there has been considerable interest in understanding the variability of the AMOC across timescales, from interannual to multidecadal (Buckley and Marshall, 2016) and millennial scales (Lynch-Stieglitz, 2017). For example, recently, several studies using comprehensive climate models found unforced millennial-scale AMOC oscillations under glacial boundary conditions (Vettoretti et al, 2022;Klockmann et al, 2020;Kuniyoshi et al, 2022;Romé et al, 2022), which resemble the Dansgaard-Oeschger events found in paleoclimate records. However, at intermediate, (multi-)centennial timescales, the variability of the AMOC has been studied less extensively, and we will focus on these timescales in the remainder of this study.…”
Section: Introductionmentioning
confidence: 95%
“…The different spatiotemporal patterns and amplitudes of AMOC variation point to different modes of operation, although the millennial-scale DO mode may also rely on a meridional salt oscillation as suggested previously (41,(44)(45)(46). A key characteristic of a DO-type cycle is the formation of a strong halocline in the North Atlantic covered by a winter sea-ice lid extending southward to the Bay of Biscay during the cold stadial phase (28,44,(47)(48)(49). This suppresses surface heat loss from the subpolar ocean and prevents convection and deep-water formation.…”
Section: Discussionmentioning
confidence: 84%
“…A key characteristic of a DO-type cycle is the formation of a strong halocline in the North Atlantic covered by a winter sea-ice lid extending southward to the Bay of Biscay during the cold stadial phase ( 28 , 44 , 47 49 ). This suppresses surface heat loss from the subpolar ocean and prevents convection and deep-water formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been considerable interest in understanding the variability of the AMOC across timescales, from interannual to multidecadal (Buckley and Marshall 2016) and millennial scales (Lynch-Stieglitz 2017). For example, recently, several studies using comprehensive climate models found unforced millennial-scale AMOC oscillations under glacial boundary conditions (Vettoretti et al 2022;Klockmann et al 2020;Kuniyoshi et al 2022;Romé et al 2022), which resemble the Dansgaard-Oeschger events found in paleoclimate records.…”
Section: Introductionmentioning
confidence: 78%